Memórias de leitura e de leitores(as) de professores(as) de literatura da educação básica: diálogos entre semiótica e letramento literário - Ferreira, Gislene Pires de Camargos (2020)
This thesis is a research linked to the Gesture - Group of Studies of the Direction of the Tocantins. It is an interdisciplinary research that puts into dialogue literary literacy, teaching and discursive semiotics to analyze stories of life stories and teacher training. The data were generated in semistructured interviews with nine teachers who work in the basic education of the public network of the State of Tocantins, in which their memories of readers emerge. We aim to relate the life histories of these readers with the school universe. In this attentive listening to the experience, we are interested in the sensitive view that the subjects throw on their relations with the text and the teaching of reading, starting from the assumption that these narratives can contribute in a significant way to understand the process of formation of readers, involving both the institutionalized school environment and other social spaces such as the family and the community. From the point of view of literary literacy, we search for works that move towards the subjective reading, observing elements that define both the meanings they attribute to the texts and what cooperates for their reading interests. In the semiotic perspective, we are mobilizing the narrative syntax, observing the subjective and object relations, understood respectively as the ones that are constituted between different subjects in different thematic and actantial roles and those of conjunction and disjunction with the books conceived as either object value, or as a sensitive object. Thus, it is important to mention that the formation of readers (as) pervades the family, school and community, that is, such a formation is complex and multifaceted, like the reader, who develops under order and chaos. Thus, it encompasses the human being in its totality, being indispensable to take into account the intelligible and the sensitive, the individual and the collective, once the stories of readings are confused with the life itself, drawing new itineraries and forging new paths towards to a humanization that is more sensitive and humanizing, allowing alterity to become a continuous presence in our interactions, whether in the school context or in other social relations, after all we know how far we have yet to progress with respect to the most sensitive human interactions , aesthetic and loving.